A comparative study of Cross and Carreau fluid models having variable fluid characteristics. (December 2022) - Salahuddin, T.; Awais, Muhammad
Abstract: The aim current work is to examine the comparison analysis of two non-Newtonian fluids (Carreau and Cross) moving in a squeezed channel across two infinite plates. A microcantilever sensor is placed in the channel. The heat transformation analysis is investigated by the heat absorption effect, variable thermal conductivity and thermal radiation. The phenomenon of concentration transfer is studied via chemical reaction and variable mass diffusion. The physical phenomenon of flow model is translated in the form of PDEs by fundamental laws, such as conservation of momentum, energy and mass transfer. It is difficult to calculate the analytical solution of determining PDEs due to nonlinear nature. Therefore the boundary layer approximation utilizes the flow relating differential equations. The dimensionless form of these ODEs is established by using similarity variables. The results are found with the help of well-defined numerical approach 'Shooting method'. The permeable velocity and Weissenberg number makes the reduction in the velocity field. In shear thinning case, velocity declines of both Carreau and Cross fluid. The temperature grows due to thermal radiation and declines due to heat absorption coefficient. The declined impact of chemical reaction is noted on the mass transfer and increment happens for higher values of mass diffusion coefficient. The required results are note down with graphical manner.